(untitled) (Al-Qamar, 2022)
The concept of equality was not mandatory. The Holy Quran, a complete guide for Muslims, provides clear protection in the areas of marriage, divorce, and inheritance. This is a significant improvement over the situation of women in pre-Islamic societies where women were the burden of the family and women were the burden. Buried alive. Nevertheless, historical circumstances have often put Muslim women at a disadvantage for centuries. Pervasive traditions of male authority and honor make it difficult for women to claim the rights guaranteed in the Quran. Numerous reforms have taken place in this century to improve educational opportunities and promote the emancipation of women in general. However, certain patterns of difficulty still dominate, such as key issues, such as employment and political activity, or issues considered divisive. Western countries viewed Muslim women as "progress" and "problem" problems, pointing to clear inequalities in the relative status of men and women. This study argues that the relationship between women and men is largely incomprehensible unless one tries to examine it from an Islamic perspective. The Quran lists men as protectors of women, and women’s justice is defined by their obedience to them. A major theme of modern Islamic scriptures is that women hold power through their innate qualities and traits and have well-defined roles in any society, preserving the roles assigned to men. This is well-explained and expressed for both men and women. Owing to the nature of the situation, it cannot be used appropriately. Their physical and psychological differences determine each individual’s different but complementary duties. Few Muslim women, even those who are critical of the restrictions imposed by Islam, understand many of the things that are considered characteristic of Western feminism. Islam frees women from many of the problems and worries inherited by men; however, women often do not give up this easily.